The study of the changes in activity of SOD in pathophysiology of gastric cancer depending on the stage of disease - H. H. Zakaryan; F. P. Sarukhanyan; G. A. Hovhannisyan; N. H. Barkhudaryan (ՀՀ ԳԱԱ հրատ.)
Superoxide dismutase (SOD) is an antioxidant enzyme that plays an important role in the defense system of the body. The aim of this study was to investigate the changes in activity of superoxide dismutase (SOD) in the plasma and tumor tissue of patients with gastric cancer depending on the stage (I-IV) of disease. It has been shown that SOD activity in the plasma of gastric cancer patients is significantly reduced compared with SOD activity in the plasma of healthy donors. In the same time tumor tissue SOD activity is increased compared with healthy (histologically examined) control tissue. The results obtained indicated that changes of SOD activity in plasma and tumor tissue of gastric cancer patients depend on the stage of disease. Супероксиддисмутаза (СОД) - антиоксидантный фермент, который играет важную роль в системе защиты организма. Целью данной работы было исследование изменений активности супероксиддисмутазы (СОД) в плазме и опухолевой ткани пациентов с раком желудка в 167 зависимости от стадии (I-IV) заболевания. Было показано, что активность СОД в плазме пациентов с раком желудка значительно снижается по сравнению с активностью СОД в плазме здоровых доноров. В то же время, в опухолевой ткани активность СОД возрастает по сравнению с активностью фермента в здоровой (гистологически исследованной), контрольной ткани. Полученные результаты показали, что изменения активности СОД в плазме и ткани пациентов с раком желудка зависят от стадии заболевания. Սուպերօքսիդդիսմուտազը (ՍՕԴ) հակաօքսիդանտային ֆերմենտ է, որը կարևոր դեր է խաղում օրգանիզմի պաշտպանողական համակարգում: Այս հետազոտության նպատակն էր ուսումնասիրել ՍՕԴ-ի ակտիվության փոփոխությունը ստամոքսի քաղցկեղով հիվանդների արյան պլազմայում և ուռուցքային հյուսվածքում՝ կախված հիվանդության զարգացման փուլից (I-IV): Ցույց է տրվել, որ ստամոքսի քաղցկեղով հիվանդների արյան պլազմայում ՍՕԴ-ի ակտիվությունը նշանակալիորեն նվազում է առողջ դոնորների արյան պլազմայում ՍՕԴ-ի ակտիվության համեմատ: Միևնույն ժամանակ, ուռուցքային հյուսվածքում ՍՕԴ-ի ակտիվությունն աճում է առողջ (հյուս¬վածաբանորեն զննված) ստուգիչ հյուսվածքում ՍՕԴ-ի ակտիվության համեմատ: Ստացված տվյալները ցույց են տալիս, որ ստամոքսի քաղցկեղով հիվանդների պլազմայում և ուռուցքային հյուսվածքում ՍՕԴ-ի ակտիվության փոփոխությունը կախված է հիվանդության փուլից:
Keywords: Biology